Impact of two accidentally introduced Encarsia species (Hymenoptera: Aphelinidae) and other biotic and abiotic factors on the spiralling whitefly Aleurodicus dispersus (Russell) (Homoptera: Aleyrodidae) in Benin, West Africa - D'Almeida, Y.A.; Lys, J.A.; Neuenschwander, Peter; Ajuonu, O. (Informa UK Limited, 1998)
In early 1993, the spiralling whitefly, Aleurodicus dispersus (Russell), was observed in Benin for the first time, inflicting damage to ornamental and shade trees and cassava. The parasitoids Encarsia ?haitiensis Dozier and E. guadeloupae Viggiani were observed in the second half of 1993. They were known to have the same host in the Pacific region, and were thought to have been introduced accidentally. The impact of these parasitoids was quantified using four surveys from 1993 to 1995 (on 2541 trees in 537 localities) and by population studies on guava. In 1993, A. dispersus occurred mostly in towns in the southern part of Benin; penetration into farmland was observed later. E. ?haitiensis was more abundant and widespread than E. guadeloupae , and by 1995 it had been recovered from most (84%) of the infested localities. On guava trees, the annual peaks of A. dispersus population declined by ca. 80% between 1993 and 1996. During the same period parasitism rates increased. Econometric multiple regression analyses based on 996 infested trees demonstrated that A. dispersus population densities, the proportion of infested trees and damage scores all declined significantly with increasing duration of the presence of the parasitoids, indicating their impact. Other variables were also significantly related to A. dispersus levels.